2021
DOI: 10.9734/ijpss/2021/v33i1730555
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Novel Organic Liquid Nutrient and Novel Plus Organic Liquid Nutrient on Quantitative Traits of Indian Bean [Lablab purpureus (L.) Sweet]

Abstract: Background: Indian bean is established as a prime vegetable crop in India and it attracts a huge market in its seasonal time period due to its multiple uses. Using of organic liquid fertilizer is demand of recent era. Concept of application of organics is vegetable crops is recent trend as it improves yield and helps to extent growth without any adverse effects on ecosystem. Methods: In this experiment, two organic based nutrient formulations viz. Novel organic liquid nutrient and Novel Plus organic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…More photosynthates were naturally created by the larger leaf area and the transit of these photosynthates from source to sink may have contributed to the rise in the number of clusters per plant. These results are in close conformity with the findings Champaneri (2021) [2] in Indian bean and Manani (2019) [5] in cluster bean, respectively. The increase in length of green pod may be due to presence of gibberellic acid in novel plus, which may speed up the cell elongation process that is responsible for the reported results (Naik, 2006) [6] .…”
Section: Yield Parameterssupporting
confidence: 92%
“…More photosynthates were naturally created by the larger leaf area and the transit of these photosynthates from source to sink may have contributed to the rise in the number of clusters per plant. These results are in close conformity with the findings Champaneri (2021) [2] in Indian bean and Manani (2019) [5] in cluster bean, respectively. The increase in length of green pod may be due to presence of gibberellic acid in novel plus, which may speed up the cell elongation process that is responsible for the reported results (Naik, 2006) [6] .…”
Section: Yield Parameterssupporting
confidence: 92%
“…It was also reported that GA3 increasing plasticity of the cell wall followed by hydrolysis of starch to sugars which lowers the water potential of cell, resulting in the entry of water into cell causing elongation. These results are in accordance with other researchers viz., [7,8] in cauliflower; [9,10,11] in cabbage in cluster bean and [12] in Indian bean.…”
Section: Resultsmentioning
confidence: 99%
“…Horticulture especially vegetable crops tribute vital contribution in this agricultural GDP which makes it more reliable crop. Vegetables are good source of vitamins, minerals and other beneficiary elements which makes it protective food for mankind and considering this fact Indian council of medical research (ICMR) have recommended a daily uptake of 300 g vegetables/day including 125 g green leafy vegetables, 100 g root vegetables and 75 g other vegetables [2]. Contribution of agriculture towards Indian GDP can be increase with right selection of crop and applying accurate amount of irrigation water.…”
Section: Introductionmentioning
confidence: 99%